Knowledge Of Diastasis Recti Abdominalis: : A Descriptive Study Of Women Of Reproductive Age - Lasiyati Yuswo Yani (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Diastasis Recti Abdominis (DRA) is a separation of the rectus abdominis muscle along the linea alba, which is common in pregnant and postpartum women. Many mothers are unaware of this condition, which can cause lower back pain, incontinence, and abdominal aesthetic issues. The purpose of this study was to evaluate the level of knowledge and understanding of DRA among women of childbearing age, as well as its impact on physical health. Methods: This was a descriptive or cross-sectional study using a questionnaire among women of childbearing age. A structured questionnaire that has passed the test for reliability and reliability was used.Results: The study often shows that mothers' knowledge of DRA is still lacking. Many mothers do not know how to check for DRA or safe physical exercise. Conclusion: Comprehensive education is needed regarding the prevention, early detection, and management of DRA through appropriate postpartum exercise to improve mothers' quality of life.